Pemberdayaan Masyarakat melalui Transformasi Limbah Dapur Menjadi Produk Bernilai Guna: Pembuatan Deterjen Cair berbasis Eco Enzym - Ria Chandra Kartika; Gamasiano Alfiansyah; Selvia Juwita Swari; Mudafiq Ryan Pratama; Imam Abrori (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Household organic waste such as fruit and vegetable scraps can be utilized as the main ingredient for eco enzyme, which serves as a natural and environmentally friendly base for liquid detergent production. This community service activity aims to empower local residents to transform kitchen waste into useful products that contribute to pollution reduction. The methods included education sessions, eco enzyme production training, liquid detergent formulation, and hands-on practice. The target group was the PKK women’s organization of Puger Kulon Village, Puger District, Jember Regency, who play an essential role in household waste management. The results showed an increase in participants’ knowledge and skills in independently producing liquid detergent. The product proved effective for household cleaning and has the potential to develop into a small-scale business opportunity. This program is expected to encourage the adoption of a green lifestyle and raise community awareness of sustainable waste management practices.